(untitled) (Research Nepal Journal of Development Studies, 2021)
As the process of digitalization spreads globally, daily dependence on cyberspace is increasing. With the rise of criminal incidents in cyberspace, it has begun to pose security threats that disrupt peace and order. In a chaotic situation with the global pandemic of Coronavirus disease (COVID-19), digitalization has become a mandatory process in the world. Along with the mandatory process of digitization and increasing trend of digitalization in Nepal, there is also a possibility of security threat. This research paper seeks and examines policies and laws that the Government of Nepal has formulated to reduce the security threat and it explored to find out what types of security threats were seen from cyberspace in Nepal during several lockdown periods during 2020 AD. The study concludes that Nepal has laws to legalize digital activities with constitutional rights to do cyber activity. But does not have enough laws and policies to address the emerging cyber threat environment because of the long process of passing the law and lack of sufficient interest and knowledge on lawmakers. The risk of cyber security in Nepal seems to be high due to non-implementation of the policies and rules issued by the government itself, low level of cyber security awareness among the people, lack of strong defense system and policy on cyber-attacks.